Biodiversity of Marine Microbes - Genitsaris, Savvas (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book entitled "Biodiversity of Marine Microbes" aims at highlighting the significance of marine microbes as primary producers, their contribution in complex ecological processes and their roles in biogeochemical cycles and ecosystem functioning. The book includes five research papers covering the diversity and composition of marine microbial communities representing all three domains of life in various marine environments, including coastal eutrophic areas, ice waters, and lagoons. One paper examines the diversity and succession of bacterial and archaeal communities from coastal waters in mesocosm experiments. The combination of classical tools with novel technological advances implemented in the methods of the papers offered an opportunity to answer fundamental questions and shed light on the complex and diverse life of marine microbes.